Volume 10B: Structures and Dynamics 2020
DOI: 10.1115/gt2020-15212
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Response and Stability of an Experimental Overhung Compressor Mounted With a Squeeze Film Damper

Abstract: This paper presents rotordynamic data obtained within a test facility studying the aerodynamics of a high-speed centrifugal compressor for aero-engine applications. The experimental overhung compressor is supported by two rolling element bearings. The compressor-end ball bearing is supported by an oil-fed squeeze film damper. After some period of operation, the compressor began to exhibit a unique nonlinear increase in the rotordynamic response followed by an unexpected subsynchronous whirl inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Luo et al [32] studied the nonlinear vibration of a single rotor-bearing system containing SFDs, analyzed the bifurcation phenomenon at different points on the rotor, and compared the dynamic response at different positions; their results showed that the nonlinear force at the support caused both the vibration response and the bifurcations of the spool at different parts to differ. Gooding et al [33] used experiments and finite element methods to study a highspeed centrifugal compressor for aeroengine applications; their results showed that effective weight of the damper support may change the second critical speed of the rotor system; increasing the weight of the damper, the second critical speed drops rapidly. Ma et al [34] established a finite element model of an aeroengine dual-rotor system with SFD and carried out a comparative study of the influence of SFD on the response of the rotor's nonlinear system.…”
Section: Responses Of the Turbine Shared Support Rotorbearing Systemmentioning
confidence: 99%
“…Luo et al [32] studied the nonlinear vibration of a single rotor-bearing system containing SFDs, analyzed the bifurcation phenomenon at different points on the rotor, and compared the dynamic response at different positions; their results showed that the nonlinear force at the support caused both the vibration response and the bifurcations of the spool at different parts to differ. Gooding et al [33] used experiments and finite element methods to study a highspeed centrifugal compressor for aeroengine applications; their results showed that effective weight of the damper support may change the second critical speed of the rotor system; increasing the weight of the damper, the second critical speed drops rapidly. Ma et al [34] established a finite element model of an aeroengine dual-rotor system with SFD and carried out a comparative study of the influence of SFD on the response of the rotor's nonlinear system.…”
Section: Responses Of the Turbine Shared Support Rotorbearing Systemmentioning
confidence: 99%